The assesement of the shunt active filter efficiency under varied power supply source and load parameters - Yuriy Sychev; Boris Abramovich; Veronika Prokhorova (International Journal of Electrical and Computer Engineering (IJECE), 2020)
The results of theoretical and experimental studies on the problems of effective application of shunt active filters for power quality improvement and electromagnetic compatibility ensuring were presented in this article. Based on the different theories and methods, the most effective and well-studied control algorithms of shunt active filters were determined and analyzed to ensure their effective application in distributed generation systems and combined power supply systems. Mathematical and computer simulation models of shunt active filters with different control algorithms in distributed generation systems and combined power supply systems were developed. According to the results of mathematical modeling and computer simulation, the dependences were detected, reflecting the influences of internal and external parameters on the factors, determining the efficiency of the correction of power quality indicators. The range of permissible changes in the parameters of shunt active filters by saving the required efficiency level of power quality correction was detected under varied power supply system characteristics, load parameters and also in hybrid structures. The adaptive algorithm of the shunt active filter functioning under varied application conditions for automated power quality improvement is developed on the basis